Implikasi Hukum Pidana terhadap Perluasan Kewenangan TNI Pasca Undang-Undang Nomor 3 Tahun 2025: Studi Perbandingan Indonesia, Belanda, dan Amerika Serikat - Junendyan Haryosatrio Dewandaru Manikingrat; Riska Andi Fitriono; Hartiwiningsih Hartiwiningsih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The juridical issues concern the limits of military criminal jurisdiction, patterns of sentencing for soldiers, command responsibility, and their implications for the principles of civilian supremacy and equality before the law. This study aims to analyze the implications and provide a comparative assessment of the expansion of the Indonesian National Armed Forces’ (TNI) authority following Law Number 3 of 2025 concerning the Amendment to Law Number 34 of 2004, particularly in relation to the addition of civilian positions that may be occupied by active-duty soldiers and the expansion of Military Operations Other Than War (OMSP). This research employs a normative juridical method with statutory, conceptual, and comparative approaches, using data sources in the form of legislation as well as national and international legal literature, which are analyzed qualitatively with deductive reasoning in drawing conclusions. The results of the study indicate that, first, the criminal law implications of the post-expansion of the TNI’s authority and roles give rise to the potential emergence of official offenses (delicta propria), particularly in the implementation of OMSP and the assignment of active-duty soldiers to civilian positions, which may generate ambiguity in judicial forums and criminal accountability; and second, a comparison with the military sentencing systems in the Netherlands and the United States demonstrates the importance of clear classification of offenses, a clearer separation between military jurisdiction and civilian courts, and the strengthening of due process of law, as well as effective civilian oversight to ensure the professionalism and legal certainty of the TNI.